Teaching Recount Text at the Tenth Grade of Office Administration Department of SMK N 1 Banyudono in 2015/2016 Academic Year - Maharani, Suci (2016)
This study focuses on teaching writing recount text at the tenth grade of Office Administration Department of SMK N 1 Banyudono. This study is aimed at describing the process of teaching recount text, teaching objective, curriculum, syllabus, roles of teacher and the students, material, the approach of teaching writing, assesment, and the problems faced by the teacher and students. This research is a descriptive qualitative research. The subject of this study is the English teacher and the tenth grade students of Office Administration Department. The methods of collecting data are observation, content of document analysis, and interview. In analyzing data, the writer uses an interactive model, namely, data reduction, data display, and conclusion. Based on the research finding, the objective in teaching recount text is to expected the students to produce the recount text both orally and in written form. The curriculum is the 2013 Curriculum. The syllabus is theme-based syllabus. The roles of teacher are as monitor, motivator, controller, model, material developer, and evaluator. The students' roles are as listener and performer. The teacher brings another material which is suitable with the topic. The teacher does not always implement all of four steps of genre-based approach, namely, Building Knowledge of Field (BKOF), Modeling of Text (MOT), Joint Construction of Text (JCOT), and Independent Construction of Text (ICOT). The assesment used in assessing writing is analytic scoring. The problems faced by the teacher are; 1) classroom management, 2) limited time, and 3) different capability of the students. The problems faced by the students are; 1) distinguishing verb, 2) developing idea, and 3) lack of vocabulary. Keywords : problems faced by the teacher and the students, teaching recount text